Bioprospecting for Microorganisms in Peloids—Extreme Environment Known for Its Healing Properties - Vadlja, Denis; Bujak, Maro; Čož-Rakovac, Rozelindra; Roje, Marin; Čižmek, Lara; Horvatić, Anita; Svetličić, Ema; Diminić, Janko; Rakovac, Saša; Oros, Damir; Zucko, Jurica; Starcevic, Antonio (Frontiers in Marine Science, 2022)
Seawater is an environment in which numerous microorganisms evolve, some with great potential for biotechnology. In recent years, many scientists have moved away from the assumption that the origin of life was in pools of water, and instead propose that life on Earth probably originated in accumulations of warm, nutrient-rich mud. This mud, also called peloid is a rich source of organisms that, due to their adaptation to this unique environment, produce a wide variety of primary and secondary metabolites with numerous and diverse activities, including anti-cancer, anti-inflammatory, antiviral, and immunomodulatory ones. In this research, two questions were addressed using collected samples of a localized peloid with demonstrated healing properties. First the biodiversity in this ecological niche was explored in order to assess the microbial communities present in it and second natural products were screened for in order to assess whether their set of predicted activities could be linked to demonstrated healing properties reported. The use of peloids in medical therapy dates back to ancient times. Abiotic components such as clay and mineral water are believed to be the main components of the healing properties of natural peloids. The places where peloids are usually found are characteristically shallow and enclosed lagoons. The constant UV exposure and increased salt concentration classifies peloids as an extreme environment. The spectrum of claims for which peloid therapy provides relief ranges from purely cosmetic, skin-related, musculoskeletal to immunological problems. These claims can hardly be supported by mineral content and heat-retaining properties alone. However, organic compounds from decaying microorganisms as well as secondary metabolites could help explain the observed range of health benefits. The fact that the relationship between the therapeutic activity of peloids and their composition outside the range of mineral and physicochemical properties has not been adequately studied indicates untapped biotechnological potential.